Apparent diffusion coefficient and tumor volume measurements help stratify progression-free survival of bevacizumab-treated patients with recurrent glioblastoma multiforme. Issue 4 (August 2019) - Buemi, Francesco; Guzzardi, Giuseppe; Del Sette, Bruno; Sponghini, Andrea P; Matheoud, Roberta; Soligo, Eleonora; Trisoglio, Alessandra; Carriero, Alessandro; Stecco, Alessandro
Background: The aim of this study was to determine whether apparent diffusion coefficient (ADC) bi-component curve-fitting histogram analysis and volume percentage change (VPC) prior to bevacizumab treatment can stratify progression-free survival (PFS) and overall survival (OS) in patients with glioblastoma multiforme (GBM) on first recurrence. Methods: We retrospectively evaluated 17 patients with recurrent GBM who received bevacizumab and fotemustine ( n = 13) or only bevacizumab ( n = 4) on first recurrence at our institution between December 2009 and July 2015. Both T2/FLAIR abnormalities and enhancing tumor on T1 images were mapped to the ADC images. ADC-L and ADC-M values were obtained trough bi-Gaussian curve fitting histogram analysis. Furthermore, the study population was dichotomized into two subgroups: patients displaying a reduction in enhancing tumor volume of either >55% or <55% between the mean value calculated at baseline and first follow-up. Subsequently, a second dichotomization was performed according to a reduction in the T2 / FLAIR volume >41% or <41% at first check after treatment. OS and PFS were assessed using volume parameters in a Cox regression model adjusted for significant clinical parameters. Results: In univariate analysis, contrast-enhanced (CE)-ADC-L was significantly predictive of PFS ( p = 0.01) and OS ( p = 0.03). When we dichotomized our sample using the 55% cut-off for enhancing tumor volume, CE-VPC was able to predict PFS ( p = 0.01) but not OS ( p = 0.08). In multivariate analysis, only the CE-ADC-L was predictive of PFS ( p = 0.01), albeit not predictive of OS ( p = 0.14). CE-ADC-M, T2/FLAIR-ADC-L, T2/FLAIR-ADC, and T2/FLAIR VPC were not significantly predictive of PFS and OS ( p > 0.05) in both univariate and multivariate analysis. Conclusions: CE-ADC and CE-VPC can stratify PFS for patients with recurrent glioblastoma prior to bevacizumab treatment.